Waiting Territories in the Americas Life in the Intervals of Migration and Urban Transit - Vidal, Laurent (Cambridge Scholars Publishing, 2016)
Mobility and displacement are major characteristics of contemporary societies. These population shifts are far from fluid, homogeneous or linear, but are, instead, interspersed with a range of longer or shorter periods of waiting. Whether these intervals are technically, administratively or politically motivated, they are often understood in spatial terms: waiting societies have a territorial dimension. This volume examines and assesses the many forms that waiting territories take, in order to better understand their various juridical statuses, their relationships with their spatial environment and specific forms of temporality, and the various economic and social relationships which they foster.The contributions primarily focus on the Americas because this continent is the product of the (voluntary or forced) displacement of various population groups that have themselves left their mark on the territories which they have appropriated. The book is divided into five parts. Part I, "The Genealogy and Stakes of Waiting Situations", presents waiting as a state of mobility; Part II, '"When Waiting Defines a Territory", focuses on the spatial implications of situations of waiting; Part III, "Social Practices and Spatial Dynamics in Waiting Territories", explores the ways in which people inhabit waiting territories; Part IV, "Waiting Territories and the Challenges to Identity", examines the mutations of identity in situations of waiting; and Part V, "The Memory, Heritage, and Curation of Waiting Territories", looks at the way in which waiting territories can become the focus of heritage practices and the politics of memory
Description based on publisher supplied metadata and other sources
Keywords: Population geography; Bevölkerungsgeografie; Gesellschaft; Mobilität; USA; Aufsatzsammlung